Olfactory Outcomes After Middle Turbinate Resection in Endoscopic Transsphenoidal Surgery: A Prospective Randomized Study. (December 2022) - Hsu, Pei-Yuan; Hsieh, Li-Chun; Wang, Yu-Hsuan; Chen, Shiu-Jau; Chan, Yun-Kai; Shen, Kuang-Hsuan; Wang, Ying-Piao
Objective: Endoscopic endonasal transsphenoidal surgery is safe and effective for sellar and parasellar tumor removal. Partial middle turbinate (MT) resection is sometimes performed to optimize the surgical field and facilitate postoperative care. Disturbances in olfaction are concerning because of the lack of randomized studies in this field. Study Design: Prospective randomized trial. Setting: Single academic medical center. Methods: We resected the lower halves of bilateral MTs in the resected group and laterally fractured bilateral MTs in the preserved group. Olfactory outcomes and sinonasal conditions were assessed by using the validated Taiwan Smell Identification Test and Lund-Kennedy Endoscopy Score, respectively. Forty-nine patients were enrolled in the final analysis, of whom 23 underwent partial MT resection. Results: The average Taiwan Smell Identification Test result was 36.9 one month after surgery, with a significant change of −4.4 ± 3.1 (mean ± SD; P < .01) from baseline. The impact was not significant at 3 months (−2.1 ± 2.6, P = .13) or 6 months (0.3 ± 2.0, P = .79). Between the MT resection and preservation groups, there were no significant differences at postoperative 1 month ( P = .60), 3 months ( P = .86), and 6 months ( P > .99). Lund-Kennedy Endoscopy Score was still higher at 3 months ( P = .006) after surgery but returned to the preoperative level at 6 months ( P = .63). Conclusions: Endoscopic endonasal transsphenoidal surgery may affect olfaction at 1 month after surgery, and olfactory function is expected to return after 3 months. Partial MT resection did not result in additional olfactory loss. It is safe to perform partial MT resection during surgery without compromising the olfactory outcomes.